First zoeal stage of ?Cataleptodius parvulus (Fabricius, 1793) and Xanthodius denticulatus (White, 1848) (Decapoda: Brachyura): larval evidences and systematic position - Barros-Alves, Samara De P.; Alves, Douglas F.r.; Bolla, Eduardo Jr Antônio; Cobo, Valter José; Negreiros-Fransozo, Maria Lucia (Zootaxa, 2013)
The first zoeal stages of ?Cataleptodius parvulus and Xanthodius denticulatus are described and compared with zoeae of other members of the subfamily Xanthinae. The larvae of ?C. parvulus and X. denticulatus differ mainly in: 1) spinulation of rostral and dorsal spines; 2) type of antenna; 3) setation of the basis of first maxilliped; and 4) type of telson. Features common to both species include a carapace provided with well-developed spines on the dorsal (1), rostral (1), and lateral (2) portions; and the antennal protopod and rostrum similar in length. The morphological differences between the zoea I of X. denticulatus and ?C. parvulus are nevertheless consistent enough to suggest that these species do not belong to the same genus Xanthodius Stimpson, 1859 as previously supposed. Also we presume that ?C. parvulus does not belong to the genus Cataleptodius.